Effect of intraperitoneal bupivacaine on postoperative pain and sympathoadrenal response following laproscopic cholecystectomy - Gotiwale, Kamlesh Govind; Patkar, Geeta A. (International Journal of Research in Medical Sciences, 2017)
Background: Pain after laproscopic surgeries is highest in the upper abdomen. Pain is greatest after operation and decreases within 24 hours. Due to adverse effects of opoids, multimodal analgesia with smaller doses of opoids, local anaesthatics and NSAIDS is given. The aim of postoperative pain relief is to provide subjective comfort and to blunt the autonomic and somatic responces to pain to inhance restore normal function.so that patient can go home early. Methods: 30 Patients each of study group (bupivacine) and control group (normal saline) of class 1 and class 2 of American society of anaesthiology of either sex were taken. 20cc of bupivacine or normal saline sprayed in gall blader fossa. Vital parameter visual analog scale score and blood sugar was noted. Results: The two groups were comparable regarding age, sex and body mass index. VAS score was significantly reduced in study group. Mean blood sugar showed no significant difference in two groups. Conclusions: Intraperitonial instillation of bupivacine is safe and reduces pain in early postoperative period.